BIOLOGICAL AND SYNTHETIC MATERIALS IN RECONSTRUCTIVE SURGERY FOR BREAST CANCER TREATMENT (LITERATURE REVIEW) - A. D. Zikiryakhodzhaev; I. M. Shirokikh; N. V. Ablitsova; M. V. Ermoshchenkova; N. V. Kharchenko; E. K. Saribekyan; A. Yu. Tukmakov; A. S. Sukhot'ko; G. M. Zapirov; Sh. G. Khakimova (ABV-press, 2018)
During the last years has been a worldwide trend towards rejuvenating breast cancer, and the evolution of reconstructive breast surgery is proceeding at a rapid pace. The surgical method is the primary method in the combined and complex treatment of breast cancer, and radical mastectomy is still the main option for surgical treatment in most Russian clinics. Most women who need a mastectomy prefer a one-stage breast reconstruction, because the woman is quickly rehabilitated psychologically and physically after this operation. Nevertheless, the use of silicone endoprostheses did not solve the problems of breast reconstruction in combined treatment in oncology. The issue remains unresolved of various complications, related not only to infections, but also to the development of capsular contracture after radiotherapy. Many patients with a one-stage breast reconstruction using a silicone endoprostheses lack the volume of their own tissues for reliable shelter of the endoprosthesis. In such cases, synthetic reticulated implants, biological implants or autologous flaps are used to cover and strengthen the lower slope of the reconstructed breast.